2017
DOI: 10.1126/sciadv.1700041
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury uptake and degradation by methanotrophs

Abstract: Certain methanotrophs can take up and degrade methylmercury, signifying a potentially important demethylation pathway in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 45 publications
2
93
0
Order By: Relevance
“…We have also shown methanobactin can bind methylmercury (99), suggesting that methanobactin can also control its bioavailability. Indeed, we have found that M. trichosporium OB3b takes up and degrades methylmercury (100). This is surprising, as merB, encoding organomercurial lyase, is not present in the genome of M. trichosporium OB3b, indicating that this strain uses another mechanism to demethylate methylmercury.…”
Section: Implications Of Methanobactin-metal Interactionsmentioning
confidence: 87%
“…We have also shown methanobactin can bind methylmercury (99), suggesting that methanobactin can also control its bioavailability. Indeed, we have found that M. trichosporium OB3b takes up and degrades methylmercury (100). This is surprising, as merB, encoding organomercurial lyase, is not present in the genome of M. trichosporium OB3b, indicating that this strain uses another mechanism to demethylate methylmercury.…”
Section: Implications Of Methanobactin-metal Interactionsmentioning
confidence: 87%
“…Two pathways have been proposed for microbial MeHg demethylation: the reductive pathway that first cleaves MeHg to Hg(II) and CH 4 by an organomercurial-lyase enzyme encoded by merB and then to Hg(0) by mercuric reductase encoded by merA of Hg-resistant bacteria (46)(47)(48)(49)(50), as well as by the oxidative pathway that completely oxidizes MeHg to CO 2 and Hg(II) by SRP and methanogens (51)(52)(53)(54). More recently, a methanotroph was also reported to degrade MeHg via the potential activity of methanol dehydrogenase (55). To gain insight into the detailed mechanisms that determine the fate of MeHg, further efforts should be made to assess the expression of hgcAB with the identification of MeHg demethylators and their activities in wetland ecosystems such as the Everglades.…”
Section: Discussionmentioning
confidence: 99%
“…SB2 Mbn exhibiting less selectivity for copper (144, 145). A role for Mbn in methylmercury (CH 3 Hg + ) degradation has also been suggested, although Mbn does not demethylate mercury on its own (146). It may be that the ability of Mbn to reduce methylmercury makes the substrate available to the demethylating enzyme (53, 147).…”
Section: Methanobactinsmentioning
confidence: 99%